2010
DOI: 10.1002/cncr.24840
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of childhood cancer survivors in Sweden: A population‐based study of education, employment, and income

Abstract: BACKGROUND: Studies of different national populations were indispensable for estimating the impact of illnessrelated disability on social outcomes in adult childhood cancer survivors. The effects of childhood cancer on educational attainment, employment, and income in adulthood in a Swedish setting were studied. METHODS: The study population was a national cohort of 1.46 million Swedish residents, including 1716 survivors of childhood cancer diagnosed before their 16th birthday, followed up in 2002 in registri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
115
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 34 publications
(57 reference statements)
8
115
2
3
Order By: Relevance
“…To our knowledge, only one other population‐based study of 1,716 childhood cancer survivors (born between 1963 and 1976 and aged 26–39 years at time of study) in Sweden has included both a wide spectrum of cancer types and a measure of being unable to work due to illness or disability 11. They reported that the proportion receiving economic compensation due to disability among cancer survivors overall was five times that expected from the general population (15% vs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one other population‐based study of 1,716 childhood cancer survivors (born between 1963 and 1976 and aged 26–39 years at time of study) in Sweden has included both a wide spectrum of cancer types and a measure of being unable to work due to illness or disability 11. They reported that the proportion receiving economic compensation due to disability among cancer survivors overall was five times that expected from the general population (15% vs .…”
Section: Discussionmentioning
confidence: 99%
“…It is reassuring that for all other diagnostic groups either no difference to that expected was observed (cranially irradiated leukaemia survivors; survivors of neuroblastoma, retinoblastoma, Wilms', bone or soft tissue sarcoma) or for three groups (Hodgkin's lymphoma; non‐Hodgkin's lymphoma; the ‘other’ neoplasm group) an increased chance of employment compared to expected was observed. The population‐based study conducted in Sweden11 that looked at employment status among adult survivors of childhood cancer by diagnostic group (leukaemia/lymphoma; CNS neoplasm; other cancers) also found that the only difference between survivors and controls was for CNS neoplasm survivors with a deficit of employment compared to controls (85% expected). In the French multicentre study5 again a significantly lower proportion of CNS survivors were employed (53.9%) than the general population (79.0%), and no significant difference in employment between observed and expected population rates was seen for survivors of Hodgkin's lymphoma, bone or soft tissue sarcomas, leukaemia and the ‘other’ diagnosis group.…”
Section: Discussionmentioning
confidence: 99%
“…1 About half of long-term survivors of childhood brain tumors have moderate or severe disability, 2,3 experience chronic medical conditions and significant neurocognitive impairment, 4,5 achieve significantly lower educational attainment than the general population, 6 and suffer long-term socioeconomic disadvantage 7 including disadvantage in the work place 8 and impaired health-related quality of life (HRQoL). 9,10 Early identification of factors predicting impaired HRQoL would enable rehabilitation of these patients to be started early and reduce their risk of subsequent impaired HRQoL.…”
mentioning
confidence: 99%
“…Stanley and colleagues 2 estimate that 6% of all initial admissions to hospital for traumatic brain injury result in discharge from the acute centre to a rehabilitation facility, providing a very conservative minimum estimate of postinjury rates of morbidity. Adding estimates for nontraumatic acquired brain injuries (including infection and hypoxia-ischemia), 3 stroke 4 and brain tumours 5 suggest that about 1300 children in the United Kingdom (population about 60 million) acquire major neurologic morbidity as the result of acquired brain injury each year, equivalent to the all-severity incidence of cerebral palsy. 6 Although this figure is only about 1% of the incidence of adult stroke, the impact of the disability is compounded over many years' future survival.…”
mentioning
confidence: 99%